Impact of Environmental, Social and Governance Factors on Investment Decision Among Investors in Nepal - Poudel, Utpal; Poudel, Resam Lal (Kanya Journal, 2025)
As a key aspect of sustainable finance, Environmental, Social, and Governance (ESG) considerations are gaining prominence in investment decision-making among investors worldwide. ESG factors influence investment behavior by shaping perceptions of risk, return, and corporate responsibility. This study examines the impact of Environmental, Social, and Governance (ESG) factors on investment decisions among individual and institutional investors in Nepal. A descriptive research design was used to assess investors’ awareness of ESG factors, while a causal-comparative approach was employed to analyze their impact and relationships with investment decisions. The study employed a quantitative approach, utilizing convenience sampling to collect data from 384 actively investing respondents in the Nepal Stock Exchange (NEPSE), including both individual investors and institutional investors to examine the influence of ESG dimensions on investment decisions. The findings reveal that for overall Nepalese investors environmental factors have an insignificant impact on investment decisions (β = 0.002, p = 0.963), while social (β = 0.391, p < 0.01) and governance factors (β = 0.391, p < 0.01) play a significant role. These findings highlight the need for investment firms to develop products focusing on social and governance factors, while policymakers, including SEBON and NRB, should strengthen ESG integration through regulations and incentives. Enhancing ESG transparency and promoting ESG focused portfolios can further boost investor confidence and drive sustainable investment growth in Nepal. This study offers novel empirical insights into the influence of ESG factors on investment decisions in an emerging market like Nepal, highlighting the primacy of social and governance dimensions over environmental ones among both individual and institutional investors.